2015
DOI: 10.1136/jnnp-2015-312379.18
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Fixation, Saccade and Pursuit in Posterior Cortical Atrophy

Abstract: See Antoniades and Kennard (doi:10.1093/brain/awv124) for a scientific commentary on this article.The clinico-neuroradiological syndrome posterior cortical atrophy is the cardinal 'visual dementia' and most common atypical Alzheimer's disease phenotype, offering insights into mechanisms underlying clinical heterogeneity, pathological propagation and basic visual phenomena (e.g. visual crowding). Given the extensive attention paid to patients' (higher order) perceptual function, it is surprising that there have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Each oculomotor session started with a calibration procedure. All participants underwent a predesigned protocol of eye movement recording described as below to evaluate fixation, gaze, smooth pursuit, and saccades …”
Section: Methodsmentioning
confidence: 99%
“…Each oculomotor session started with a calibration procedure. All participants underwent a predesigned protocol of eye movement recording described as below to evaluate fixation, gaze, smooth pursuit, and saccades …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have also reported impairment in the comprehension of measurement units. A recent study has noted deficits in fixation, saccade, and pursuit tasks in PCA patients which may contribute to the visual symptoms 75 . PCA patients have significant anomia and impaired phonemic fluency as well 76,77 .…”
Section: Pca Variant Of Admentioning
confidence: 99%
“…Eye-tracking technology, is rapidly developing for use in future research. 22,23 There are numerous potential benefits for using eye tracking criteria to study cognitive visual processing in AD patients. Compared with many traditional neurophysiological evaluations, eye movement recordings do not require additional behavioral responses such as pressing buttons or verbal responses to assess cognitive changes.…”
Section: Introductionmentioning
confidence: 99%